Mapping of Resistance Genes to Brown Planthopper in Untup Rajab, an Indonesian Local Rice Variety - Muhamad Yunus; Diani Damayanti; Ahmad Dadang; Ahmad Warsun; Dani Satyawan; Kusumawaty Kusumanegara; Iswari Saraswati Dewi; Sutrisno Sutrisno; Bahagiawati Amir Husin (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2018)
Brown planthopper (BPH) is a major rice pest in Indonesia. The most economical and effective approach to control the insect pest is by using resistant varieties. Exploring for resistance genes is, therefore, a prerequisite for effective breeding program for BPH resistance. This study aimed to map BPH resistance genes in Untup Rajab, an Indonesian local rice variety. Genetic map was constructed using an F2 population from a cross between TN-1 and Untup Rajab, and SNP markers from RiceLD SNP Chip. Phenotyping was performed using bulk seedling test on F2:3 seedlings against two BPH populations, i.e. X1 and S1. Four QTLswere identified on chromosomes 5, 6, 8, and 11 with PVE values of 7.63%, 9.40%, 17.66%, and 3.05%, respectively. Relatively normal distribution of resistance phenotype and the relatively low PVE values indicate that Untup Rajab has a quantitative resistance to BPH with two different resistance loci identified for each BPH test population. The QTL on chromosome 8 overlaps with OsHI-LOX gene, which is associated with resistance to BPH, and adjacent to another QTL for resistance to green leafhopper. The QTL on chromosome 6 was found near OsPLDα4 and OsPLDα5 genes which are related to BPH resistance. Meanwhile, the QTL intervals on chromosome 5 and 11 did not overlap with any known BPH QTLs or genes, which make them attractive candidates for novel BPH resistance gene discovery.